Empyema thoracis presented as giant back abscess - Siti Hafzan Abd Karim, MD; Wan Zainira Wan Zain, MMed; Mohd Nizam Mohd Hashim, MMed; Andee Dzulkarnaen Zakaria, MMed; Firdaus Hayati, DrGenSurg; Chiak Yot Ng, MMed (Elsevier, 2021)
Empyema thoracis (ET) is defined as pus in the pleural space, either localized or involving the entire pleural cavity, due to diverse etiologies. In severe form, it may infiltrate the extra- pulmonary region. Clinical guideline describes 3 stages of parapneumonic effusion before developing into an ET, namely the exudative stage, the fibrinopurulent stage, and the orga- nizing/late stage. We highlight a 59-year-old gentleman who presented a back swelling masquerading as a deep-seated abscess, in which the diagnosis of ET had not been established early. The principles of treatment are treating the underlying condition such as pneumonia, pleural drainage and debridement, full re-expansion of the collapsed lung by performing chest physiotherapy, and improving nutrition. ET is a condition with a dynamic process due to diverse etiologies, either localized or involving the entire pleural cavity. The gold standard in diagnosing ET is the pleural aspiration of fluid from the pleural space, whereas the management of ET may include non-surgical and/or surgical treatments based on the basic principles of ET treatment.